2012
DOI: 10.1152/jn.00724.2010
|View full text |Cite
|
Sign up to set email alerts
|

Egocentric and allocentric alignment tasks are affected by otolith input

Abstract: Gravicentric visual alignments become less precise when the head is roll-tilted relative to gravity, which is most likely due to decreasing otolith sensitivity. To align a luminous line with the perceived gravity vector (gravicentric task) or the perceived body-longitudinal axis (egocentric task), the roll orientation of the line on the retina and the torsional position of the eyes relative to the head must be integrated to obtain the line orientation relative to the head. Whether otolith input contributes to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 72 publications
3
28
1
Order By: Relevance
“…In fact, we found significantly higher variability for desired 75° RED whole-body roll compared to desired upright position in the earth-fixed paradigm, supporting the "all sensors' integrated hypothesis". This phenomenon was recently also reported for visual line adjustments along the body-longitudinal axis in whole-body roll-tilted positions (Tarnutzer et al 2012). Such a behavior is compatible with the previously observed whole-body roll-angle dependent increase of SVV variability, which most likely reflects head-roll dependent variability of otolith signals (Tarnutzer et al 2009a).…”
Section: For Visually-guided Self-adjustments Extra-retinal Cues Are supporting
confidence: 90%
See 3 more Smart Citations
“…In fact, we found significantly higher variability for desired 75° RED whole-body roll compared to desired upright position in the earth-fixed paradigm, supporting the "all sensors' integrated hypothesis". This phenomenon was recently also reported for visual line adjustments along the body-longitudinal axis in whole-body roll-tilted positions (Tarnutzer et al 2012). Such a behavior is compatible with the previously observed whole-body roll-angle dependent increase of SVV variability, which most likely reflects head-roll dependent variability of otolith signals (Tarnutzer et al 2009a).…”
Section: For Visually-guided Self-adjustments Extra-retinal Cues Are supporting
confidence: 90%
“…However, trial-to-trial variability of alignment tasks increases independently from the presence / absence of retinal input when the subject is roll-tilted (Tarnutzer et al 2012), so increased variability in our tasks cannot be explained solely on the basis of variability of torsional eye position. At the same time, the oblique effect diminishes when the head is rolltilted (Luyat et al 2001;McIntyre et al 2001), mostly due to increased discrimination thresholds along the principal axes.…”
Section: For Visually-guided Self-adjustments Extra-retinal Cues Are mentioning
confidence: 83%
See 2 more Smart Citations
“…Manipulations of the environment, such as obtaining the SVV while roll-tilted under water, have shown that the influence of proprioception on the SVV is minor compared with that of otolith input in healthy human subjects (Graybiel et al 1968;Jarchow and Mast 1999;Wade 1973). For visual as well as haptic line adjustments along an Earth-vertical (gravicentric) axis or a body-longitudinal (egocentric) axis, Tarnutzer and colleagues observed roll angle-dependent modulations of alignment precision in all conditions (Tarnutzer et al 2012). The comparable results in the egocentric and gravicentric (i.e., a special case of an allocentric frame) task suggest that the same mechanism is responsible for the increased trial-to-trial variability in roll-tilted positions.…”
Section: In This Study We Investigated the Potential Impact Of Directmentioning
confidence: 99%